Shadowing technique the solution for listening skill: A study at English Educations study program - Sufriady, Deddy; Sholihah, Lilis; Shalma, Diana; Agrifinna, Dinda (Universitas Lampung, 2024)
Listening is one of the key receptive skills, essential for capturing the meaning of spoken language. Developing listening skills requires frequent practice with English language inputs. Various accessible media, such as YouTube videos and podcasts, provide valuable resources for enhancing these skills. However, while media play an important role, teaching methods and techniques are equally critical to success. Many S1 Language Education students still struggle to meet the expected standards in listening proficiency. A pre-survey conducted by the researcher, involving a pre-test on students' listening skills, revealed results that were below the expected benchmark. Given this, the Shadowing Technique was introduced to help improve students' listening abilities. This study aims to examine whether there is a significant improvement in students' listening skills after being taught using the Shadowing Technique, which is supported by technology-based learning media like YouTube and podcasts.The research employed a pre-experimental quantitative method, using a one-group pretest-posttest design. The participants were 27 second-semester students from the English Education Study Program at FKIP, University of Lampung, who were enrolled in advanced listening courses. The findings revealed a notable improvement in students' listening skills after using the Shadowing Technique. This study highlights the challenges students face in improving their listening skills, especially the difficulty in understanding spoken English due to limited exposure and practice. Additionally, it suggests that incorporating technology-based media alongside effective teaching techniques can lead to significant improvements in listening proficiency. Specific indicators of improvement include increased comprehension accuracy and enhanced ability to follow and replicate spoken English. These findings offer valuable insights into the potential of shadowing in language learning.Keywords: Listening. Shadowing Techniques, Technology-Based Learning Media, Education